Néhány ikonográfiai előzmény Csontváry cédrus festményeihez - Szabó, Júlia (1978)
ersch. 1979; Studies to the Iconography of the Cedar Motif in the Paintings of Tivadar Csontváry; 387 f. engl. Résumé; auch zu den myth. Vorstellungen betreffend Zedern im Alten Orient.